Clinical manifestations of damage to the cardiovascular system and predictors of poor prognosis of Takayasu arteritis in Kyrgyz patients - G. M. Koilubaeva; A. M. Bolotbekova; M. T. Beishenkulov; O. N. Egorova; G. M. Tarasova; A. M. Lila; G. Suiunbay kyzy; A. T. Turatbekova; A. A. Okunova; M. A. Chukubaev; Z. E. Turdukulov; D. A. Usupbaeva (Научно-практическая ревматология, 2023)
Damage to the cardiovascular system (CVS) in Takayasu arteritis (AT) is characterized by a wide range of clinical manifestations and an unfavorable prognosis of the disease. Objectives: determine the characteristics of clinical manifestations of damage to the CVS and predictors of unfavorable prognosis in Kyrgyz patients with АТ. Methods: The study included 135 patients with a reliable diagnosis of AT, verified according to the classification criteria of the American College of Rheumatology/The European Alliance of Rheumatology Associations (ACR/EULAR, American College of Rheumatology/European Alliance of Associations for Rheumatology). All patients underwent clinical and standard laboratory and instrumental examination. Results: CVC lesion was observed in 84.4% of patients with AT and was manifested mainly by secondary arterial hypertension (AH) and aortic regurgitation (AR) – 52.8% and 27.8% of cases, respectively. The main cause of secondary hypertension was renovascular hypertension (63.4%). Myocarditis (8.5%) and coronary syndrome (3.8%) were significantly less frequently diagnosed. Among the cardiovascular complications (CVc) that developed in 32.5% of patients, decompensated chronic heart failure (DCHF) (48.7%) and acute cerebrovascular accident (ACVA) were the most common (40,5%). The immediate cause of death in the observed cohort was DCHF (66.7%) due to severe AR (83.3%) and ischemic cardiomyopathy (16.7%). Predictors of the development of CVc were the V anatomical type of vascular lesion, high activity of the pathological process, severity of stenotic changes, serious clinical complications (CC) and severe AR (p<0.05). Conclusion: 1. CVS lesion was observed in 84.4% of Kyrgyz patients with AT. 2. The most frequent variant of cardiovascular pathology was secondary hypertension (52.8%) caused by vasorenal (63.4%), coarctation (33%) and aortic (3.6%) changes. The second most common was pathology of the aortic valve (27.8%) with a predominance of minor AR (45.8%). 3. CVc was observed in one third of patients (32.5%) and in most cases were presented with DCHF (48.7%) and ACVA (40.5%). 4. Unfavorable factors associated with an increased risk of CVc in the observed patients were V anatomical type of vascular lesion, high activity, pronounced stenotic changes, severe CC and severe AR (p<0.05).